Rapid identification of quinone methide triterpenes using LCMS/MS approach / Dr. Humera Naz, Prof. Dr. JFF Weber and Dr. Hannis Fadzillah Mohsin - Naz, Humera; JFF, Webe; Mohsin, Hannis Fadzillah (Research Management Institute (RMI), 2016)
Medicinal plants have been used by mankind as a source of medicines since immemorial time. More than 35,000 plant species have been reported to be used in various human cultures around the world for medicinal purposes (Lewington & Network, 1993). Burkill (1966), in his extensive compilation of the economic products of the Malay Peninsula, recorded around 1,300 plants that have been used in the local traditional medicine. The diverse flora of Malaysian forest offers a great abundance of chemical diversity of secondary metabolites and bioactive compounds such as alkaloids, flavonoids, steroids, xanthones and genetic variability that have great potential to serve the needs of modern medicine (Ahmad et al., 2003). The discovery of calanolide A and their derivatives from Calophyllum lanigerum (bintangor tree) with anti-HIV activities shows the potential of the forest in the drug discovery program and the importance of a well-planned research. Other Malaysian plants such as Eurycoma longifolia (tongkat AN), Centella asitatica (pegaga), Labisia pumila (kacip Fatimah), Elephantopus scaber (tapak Sulaiman) and Phyllanthus niruri (dukung anak) also showed good potential to be developed into useful drugs (Ahmad et ai, 2003). The plant extracts of the family Celastraceae have been used throughout South America and China as insect repellents and insecticides in traditional agriculture, and also as a remedy for stomach complaints, fever, rheumatoid arthritis and cancer (Spivey et ai, 2002). Quinone methides are secondary metabolites of the Celastraceae family. It is considered as chemotoxonomic indicators due to its major presence in Celastraceae family. Pristimerin, a quinonemethide triterpenoid derived from Celastraceae, has been proven by research to suppress tumor promotion, metastasis and angiogenesis (Kim et ai 2013). The bioactive compounds from L. javanicum is not thoroughly investigated. Therefore, this study is carried out in an attempt to characterise the phtochemical constituents and biological activities of this plant.